2022
DOI: 10.1590/0103-8478cr20210141
|View full text |Cite
|
Sign up to set email alerts
|

Natural infection of Trypanosoma sp. in domestic sheep from Ecuador

Abstract: Trypanosomosis in sheep is a hemoparasitic disease of worldwide interest due to its effects on the health of animals and the economic impact on producers, is caused by the protozoan Trypanosoma sp. In the present study, the occurrence of Trypanosoma sp. in sheep from the urban-rural area of the canton Salitre was determined, through an applied study with a qualitative descriptive prospective cross-sectional approach, carried out between October 1, 2019, and February 19, 2020. Blood samples were extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(30 reference statements)
1
1
0
Order By: Relevance
“…Our study did not evidence T. evansi in any of the bovine samples from the two slaughterhouses. These values are compatible with previous studies in Ecuador, 31.0% for Trypanosoma spp and 65.5% for A. marginale in the Pastaza province (19) and 86.1% in the Santo Domingo de los Tsachilas province (22), 18.94 and 20.28% for Babesia spp in the Pichincha and Manabí provinces, respectively (25).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study did not evidence T. evansi in any of the bovine samples from the two slaughterhouses. These values are compatible with previous studies in Ecuador, 31.0% for Trypanosoma spp and 65.5% for A. marginale in the Pastaza province (19) and 86.1% in the Santo Domingo de los Tsachilas province (22), 18.94 and 20.28% for Babesia spp in the Pichincha and Manabí provinces, respectively (25).…”
Section: Discussionsupporting
confidence: 92%
“…Despite this, there is little information on bovine trypanosomosis in Ecuador; however, Coello Peralta et al found 20% positive samples of Trypanosoma spp. in sheep blood smears (18). Other studies by Medina-Naranjo et al found a seroprevalence of 31.3% for Trypanosoma spp.…”
Section: Introductionmentioning
confidence: 86%
“…Los estudios realizados en Ecuador sobre tripanosomas infectando mamíferos se han enfocado en el registro de prevalencias y en la identificación de los parásitos, aunque algunos no han logrado identificarlos hasta el nivel de especie (e.g., Coello-Peralta et al, 2020, 2022. Por lo tanto, la primera recomendación es identificar correctamente las especies de tripanosomas.…”
Section: Las Identificacionesunclassified